Healthy controls have as much bile reflux as gastric ulcer patients. Issue 12 (December 1987) - Schindlbeck, N E; Heinrich, C; Stellaard, F; Paumgartner, G; Müller-Lissner, S A
Abstract : Data on duodenogastric reflux of bile in gastric ulcer are conflicting. We therefore measured intragastric bile acid concentration and its composition from individual bile acids, duodenogastric bile acid reflux rate, gastric emptying rate, and secretion rates of volume and acid in 30 patients with gastric ulcer and in 66 healthy controls, both in the fasting state and after feeding a liquid meal. Patients had higher gastric bile acid concentrations (p less than 0.05) than controls in the fasting state, but the overlap between the groups was considerable. In fasting patients with corpus ulcer, gastric secretion rates were significantly decreased when compared with controls. There was no difference between patients and controls with respect to gastric emptying rate, bile acid reflux rate, intragastric amount of bile acids, and bile acid composition in the fasting state. Postprandially, all parameters tested were similar in patients and controls. Controls showed high reflux rates with similar frequency as did ulcer patients. We conclude that increased gastric bile acid concentrations in the fasting stomach of patients with gastric ulcer are the result of gastric hyposecretion and not of increased reflux. They probably are pathogenetically irrelevant.